Antioxidant and Antibacterial Activities of Noni Fruit (Morinda Citrifolia) Extract - Fitriana, Wiwit Denny; Fajril Islami, Mohamad (Universitas Airlangga, Campus C Mulyorejo, Surabaya, Indonesia, 2025)
Noni fruit (Morinda citrifolia), also known as noni, is widely used in Indonesia for its antioxidant and antibacterial benefits. This study evaluated the antioxidant and antibacterial activities of ethanol-extracted Noni fruit. Antioxidant activity was assessed using the DPPH method, showing an IC50 value of 28.82 μg/mL. Antibacterial activity was tested using the Resazurin Microtiter Assay (REMA), revealing MIC values against Bacillus subtilis (2.5 mg/mL), Staphylococcus aureus (10 mg/mL), Salmonella typhi (10 mg/mL), Pseudomonas aeruginosa (>10 mg/mL), and Propionibacterium acnes (0.63 mg/mL). The results indicate that Noni fruit extract has potential as a natural source of antioxidants and antibacterials.